The Problems of Urban Identity in Sociological Classics - Musiyezdov, Oleksiy (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
The article is devoted to the problems of urban identity in the classical sociological concepts (M. Weber, F. Toennis, E. Durkheim, G. Simmel, R. Park, L. Wirth). The author shows that while M. Weber argued that the presence of the urban community is a necessary condition for the existence of the city itself, the other classics prove the impossibility of existence of the urban community as a "moral unity" because of the large size, high density and fundamental heterogeneity of the urban population. It is claimed that talking about urban identity as a result of identification with the urban community is possible referring to the idea that it is "imaginary". Opportunities for choosing of identification samples provided by modern society force to reflect what the city is in this capacity. In order to answer this question it is suggested to appeal to the concept of cultural forms (cultural style).